The frequency of gastroesophageal reflux when radiofrequency catheter ablation procedures for atrial fibrillation under general anesthesia with a supraglottic device: Observational pilot study. Issue 6 (12th February 2021) - Ahn, Jin Hee; Park, Jiyeon; Jo, Jae Seong; Lee, Sung Hyun; On, Young Keun; Park, Kyoung-Min; Oh, Eun Jeong; Ko, Justin Sangwook; Jeong, Ji Seon
Abstract : Abstract: Gastroesophageal reflux (GER) in radiofrequency catheter ablation (RFCA) occurs due to vagal plexus damage during pulmonary vein isolation. We hypothesized that the frequency of GER in the oropharynx will be less compared to other areas (low-esophagus, mid-esophagus). We confirmed the frequency of GER before and after RFCA in 3 areas. We studied 30 patients who were scheduled for RFCA under general anesthesia. Anesthesia was performed using supraglottic devices (SGD) with a suction port. Two esophageal temperature probes capable of suction and measuring temperature were inserted through the suction port. The pH of the 3 areas was measured before and after the RFCA at 3 areas (mid-esophagus, low-esophagus, and oropharynx). GER was observed in 13 of 30 patients (43%). In one patient, it was observed in the oropharynx, in 4 patients it was observed in the mid-esophagus, and in 13 patients, it was observed in the low-esophagus. For patients with GER at the oropharynx and mid-esophagus, it was also observed at the low-esophagus. The difference in the pH before and after the RFCA was not significant at the oropharynx and mid-esophagus ( P  = .726 and P  = .424, respectively), but it was significantly different at the low-esophagus ( P  < .001). The total ablation time was longer in the GER group compared to the non-GER group ( P  = .021). GER after RFCA occurred in 43% of patients, only 1 patient in the oropharynx. And aspiration pneumonia after SGD extubation did not occur. Therefore, the use of SGDs in RFCA does not completely eliminate the possibility of aspiration, so care should be taken.